Dietary nitrate lowers ambulatory blood pressure in treated, uncontrolled hypertension: a 7-d, double-blind, randomised, placebo-controlled, cross-over trial. Issue 6 (19th March 2018) - Kerley, Conor P.; Dolan, Eamon; James, Philip E.; Cormican, Liam
Abstract: Dietary nitrate has been shown to increase nitrate/nitrite levels and decrease blood pressure (BP) in multiple populations. There are few reports among hypertensives and these reports have provided conflicting evidence. We aimed to assess the effect of daily nitrate compared with placebo in subjects with uncontrolled hypertension (HTN). On day 0, hypertensives wore an ambulatory BP monitor (ABPM) for 24 h and blood was taken. Subjects were then randomised to 7-d nitrate-rich beetroot juice (NO3 − ) (12·9 mmol nitrate) followed by 7-d nitrate-depleted beetroot juice (0·5 mmol nitrate) or vice versa. ABPM and blood were assessed before and after both conditions. In all, twenty subjects with treated yet uncontrolled HTN entered and completed the trial (mean age=62·5 years, mean BMI=30·7 kg/m 2 ). Baseline BP was 137/80 (sd 7/7) mmHg. Dietary nitrate was well tolerated and resulted in significantly increased plasma nitrite ( P =0·0004) and decreased 24-h systolic BP and diastolic BP compared with placebo (−8 mmHg; P =0·012 and −4 mmHg; P =0·018, respectively). Our results support the existing data suggesting an anti-hypertensive effect of dietary nitrate in treated yet uncontrolled hypertensives. Targeted dietary strategies appear promising contributors to BP control.